PEMBERDAYAAN KARANG TARUNA KARANG INDAH MELALUI PENGEMBANGAN MANAJEMEN USAHA KERAJINAN AKAR POHON DI DESA PASIR PEUTEUY PANDEGLANG - Icin Quraysin; Suhandi Suhandi; Tata Rustandi; Agus Lukman Hakim (Jurnal Abdimas Bina Bangsa, 2023)
The beautiful coral cadets of Pasir Peuteuy Village as a forum for guidance and development and empowerment in an effort to develop creative economic activities in Pasir Peuteuy Village have not been able to make a maximum contribution to the development of tree root crafts business management, so that the existence of tree root crafts businesses managed by coral members Karang Indah cadets have not been able to provide maximum results. The problems faced are: Karang Indah cadet members have not been able to develop tree root craft business management, have not been able to develop product promotion and marketing, have not been able to create interesting and contemporary handicrafts, many have do not yet understand the presence of Information Technology, there is no role from Pasir Peuteuy Village in assisting the development of tree root craft business management. The purpose of this service is to help improve the ability of Karang Indah Youth Organizations in implementing business management, making attractive tree root crafts and online marketing (e-commerce). Training methods: developing business management, making interesting and up-to-date tree root crafts, online marketing and product promotion assistance (e-commerce) and assistance from the beautiful coral youth organization to the Office of Cooperatives and UMKM in Pandeglang Regency. The results of this community service show that there is an increase in business management, members of the Karang Indah Youth Organization can create interesting and contemporary tree root crafts and can market products online (e-commerce).